The Effectiveness of Natural and Synthetic Antioxidant Additives on the Oxidation Stability of Biodiesel Synthesized from Fresh and Waste Sunflower Oilesized from fresh and waste sunflower oil - Nuhanovic, Mirza; Topalovic, Ajla; Culum, Dusan; Ibragic, Saida (Orbital: The Electronic Journal of Chemistry, 2018)
Biodiesel fuel is the realistic fuel for the future due to its environmental, economic and energetic benefits. However, the degradation and instability during biodiesel storage and application present the major disadvantages and hence a modern scientific challenge. The aim of this study was to choose optimal parameters for biodiesel synthesis from fresh and waste sunflower cooking oil and to investigate the possibilities of increasing its resistance towards oxidative degradation. Various physico-chemical characteristics essential for the quality estimation of the resulting biodiesel products were compared before testing the effectiveness of natural and synthetic antioxidants. Butylated hydroxytoluene (BHT), carvacrol and α-tocopherol were added to the biodiesel in different concentrations in order to determine their efficiency during the Schaal oven test. Results proved that both, fresh and waste oil can be valuable sources for the synthesis of biodiesel that meets European and American quality standards. Among the antioxidants, BHT was the most efficient one in both types of biodiesel and its usage would be recommended at the concentration of 1000 ppm. The findings present a cost-effective and environmentally friendly source for biodiesel production with improved properties - considerably enhanced resistance to oxidative degradation, where synthetic antioxidants are given the priority. DOI: http://dx.doi.org/10.17807/orbital.v10i7.1174